2020
DOI: 10.1002/jso.25921
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anastomotic leakage for rectal cancer oncologic outcome: A systematic review and meta‐analysis

Abstract: Background and Objective: Anastomotic leakage is a serious complication after arterial resection of rectal cancer. It has been found that anastomotic leakage is related to the oncological outcome. The purpose of the study is to evaluate the long-term outcome of the rectal tumor after anastomotic leakage. Methods:The effect of anastomotic leakage on the oncological outcome of rectal cancer was studied by electronic literature retrieval. Using the DerSimonian Laird random effect model to calculate the odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 83 publications
(81 reference statements)
2
38
0
Order By: Relevance
“…In contrast, the previous meta-analysis by Bashir et al concluded that patients with AL have a lower 5-year OS of 58% compared with 73% in nonleaking patients [24]. Moreover, the negative impact of AL on OS was indicated by Yang et al and a large Scandinavian cohort study by Stormark et al [25,26]. Our study confirmed the impaired OS and DFS in patients suffering from AL, and there is a rationale for such findings.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, the previous meta-analysis by Bashir et al concluded that patients with AL have a lower 5-year OS of 58% compared with 73% in nonleaking patients [24]. Moreover, the negative impact of AL on OS was indicated by Yang et al and a large Scandinavian cohort study by Stormark et al [25,26]. Our study confirmed the impaired OS and DFS in patients suffering from AL, and there is a rationale for such findings.…”
Section: Discussionsupporting
confidence: 78%
“…and a large Scandinavian cohort study by Stormark et al 25,26 Our study con rmed the impaired OS and DFS in patients suffering from AL and there is a rationale for such ndings. First, AL may lead to an increased rate of local recurrence because of cancer cell implantation and progression at the in amed leaking anastomotic site.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, the risk factors of AL after laparoscopic LAR may differ from those after laparotomy. Furthermore, by reviewing articles published in the past 5 years, we found out that no agreement has been achieved on whether AL has an impact on oncological outcomes or not [10,12,13]. Therefore, the present study has two clinical objectives: (1) to identify the risk factors of symptomatic AL after laparoscopic LAR based on patient, surgery, and tumor-related variables and (2) to investigate the impact of symptomatic AL on 3and 5-year overall survival rates.…”
Section: Introductionmentioning
confidence: 91%